Inventory optimization. (c2018) - Indus, Karina (2018)
This research examines the various problems in consumable inventory management within an Emergency Department (ED) of the Lebanese Academic Medical Center (LAMC). Specifically, this research supports understanding how the implementation of lean tools and quantity models can change daily operations in the inventory management of an ED. This case study has two general objectives 1) to clean and redesign the stock room and 2) develop a proper order policy. Relatedly, the ABC and 5S methods were used meet the first objective and the quantity models, EOQ and (R, s, S), were used for the second objective. Specifically within the ABC analysis, two categorization variables (value and use) were used. In developing the order quantity policy, four models were examined and a full cost analysis was performed for each. In the end, the periodic review policy with fixed reorder period was selected and tested in the field. The chosen policy proved to be efficient relative to the ED situation prior to the implementation of the selected policy. The efficiency was measured via survey with all relevant ED employees.